Інформаційні мережеві технології в науці і освіті - Zgurovsky, M. Z.; Yakimenko, Yu. I.; Timofeyev, V. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Dominant factors of information technologies that influence development of information society are adduced. Fields of information network technologies application in science and education are considered, as well as some problems of the National scientific and educational network URAN (Ukrainian Research and Academic Network) and the distance learning system in Ukraine. Possible ways of URAN integration into the European information space are examined.